Photothermal lysis of Pseudomonas aeruginosa by polyaniline nanoparticles under near infrared irradiation - Bongiovanni Abel, Silvestre Manuel (2018)
Increases in the prevalence of antibiotic resistant bacteria require new approaches for the treatment of infectious bacterial pathogens. A new therapeutic modality, which is called photothermal therapy (PTT) involves the absorption of Near Infrared Radiation (NIR) light by absorbing species (e.g. polyaniline nanoparticles) and transfer of the absorbed energy into the surrounding environment as heat that could cause pathogen death. Since the pathogen cells, and the surrounding tissue, does not absorb NIR radiation, an agent which strongly absorb the light has to be added. In this work, were performed experiments to determine if polyaniline nanoparticles (PANI-NP) in combination with NIR irradiation could be used to destroy Pseudomonas aeruginosa. Results reveal that this nanomaterial, following NIR exposure could be used for killing bacteria because it was observed a significant decrease in cell viability triggering cell death. In addition, the cell death mechanism was observed by DNA fragmentation.